760 Trough levels of ipilimumab in serum as a potential predictive biomarker of clinical outcomes for patients with advanced melanoma after treatment with ipilimumab. (9th November 2020) - Koguchi, Yoshinobu; Iwamoto, Noriko; Shimada, Takashi; Chang, Shu-Ching; Cha, John; Piening, Brian; Curti, Brendan; Urba, Walter; Redmond, William
Abstract : Background: Immune checkpoint blockade (ICB) using anti-CTLA-4 and anti-PD-1/PD-L1 has revolutionized the treatment of advanced cancer. However, ICB cures only a fraction of patients, and biomarkers such as PD-L1 expression or CXCL11 have suboptimal sensitivity and specificity. Exposure-response (E-R) relationships have been observed in other therapeutic mAbs. There are many factors that can influence E-R, 1 yet several studies have shown that trough levels of anti-PD-1/PD-L1 correlated with clinical outcomes. Little is known about the potential utility of anti-CTLA-4 levels as a predictive biomarker. Methods: Serum was obtained after doses 2 and 4 from patients with advanced melanoma who received ipilimumab alone (3 mg/kg every 3 weeks for 4 treatments) via an expanded access program. We have successfully established a proteomics assay to measure ipilimumab concentration in serum using a versatile LC-MS/MS-based nano-surface and molecular-orientation limited proteolysis (nSMOL) approach. 2 Results: Serum samples from 38 patients were assessed for the ipilimumab trough levels by the nSMOL assay. The ipilimumab concentrations after dose 2 were ranged between 4.44 and 33.63 ug/ml (median:16.30, IQR: 11.41 – 20.87). We found that patients with lower serum trough levels of ipilimumab had poorer overall survival when we grouped patients based on the ipilimumab trough level (figure1 Median survival: < median = 199.5 days, > median = 519.0 days. Log-rank test: p = 0.0057). A similar result was observed for ipilimumab trough levels after dose 4. We also found that trough levels of ipilimumab inversely associated with CXCL11 (p = 0.0095. R 2 = 0.1818), a predictive biomarker we previously identified, 3 and soluble CD25 (sCD25) (p = 0.0038. R 2 =0.2210), a prognostic biomarker for advanced melanoma but not with other biomarkers such as absolute lymphocyte counts, LDH, VEGF, sMICA, and sMICB. Conclusions: Our results suggest that the trough levels of ipilimumab might be a useful predictive biomarker for the long-term survival of the patients with advanced melanoma treated by ipilimumab. The weak association of ipilimumab trough levels with CXCL11 and sCD25 as well as no association with known biomarkers highlights the potential usefulness of trough levels of ipilimumab as the biomarker. Further studies are required to understand the mechanisms for lower levels of ipilimumab in refractory patients to improve the efficacy of ICB. Acknowledgements: This study was funded by Providence Portland Medical Foundation and Shimadzu Corporation. Trial Registration: NCT00495066 Ethics Approval: All patients provided written informed consent and all studies were carried out in accordance with the Declaration of Helsinki under good clinical practice and Institutional Review Board approval. References: Dai HI, Vugmeyster Y, Mangal N. Characterizing exposure-response relationship for therapeutic monoclonal antibodies in immuno-oncology and beyond: challenges, perspectives, and prospects. Clin Pharmacol Ther 2020. 10.1002/cpt.1953. Iwamoto N, et al. Selective detection of complementarity-determining regions of monoclonal antibody by limiting protease access to the substrate: nano-surface and molecular-orientation limited proteolysis. Analyst 2014;139:576–580. Koguchi Y, et al. Serum immunoregulatory proteins as predictors of overall survival of metastatic melanoma patients treated with ipilimumab. Cancer Res 2015;75:5084–5092.